Coastal eutrophication driven by long-distance transport of large river nutrient loads, the case of Xiangshan Bay, China - Xiangyu Sun; Jingjing Zhang; Hongliang Li; Yong Zhu; Xingju He; Yibo Liao; Zhibing Jiang; Lu Shou; Zhiwen Wang; Tim C. Jennerjahn; Jianfang Chen (Science of The Total Environment, 2024)

Editorial: Environmental change affecting COastal ecosystems of tropical China during the Anthropocene: Landward vs. OCeanic influence (ECOLOC) - Tim C. Jennerjahn; Jianfang Chen; Larissa Dsikowitzky; Hongwei Zhao (Estuarine, Coastal and Shelf Science, 2023)

Meadow trophic status regulates the nitrogen filter function of tropical seagrasses in seasonally eutrophic coastal waters - Esther Thomsen; Lucia S. Herbeck; Inés G. Viana; Tim C. Jennerjahn (Limnology and Oceanography, 2023)
The nutrient filter function is an important ecosystem service of seagrass meadows that mitigates the consequences of coastal eutrophication. In northeast Hainan in China, large seagrass areas were lost due to chronic eutrophication induced by untreated pond aquaculture effluents. However, in adjacent areas, seagrasses could survive due to seasonal exposure (i.e., not chronic) to eutrophication only. In a way, the conditions in these areas represent a transitional environment which allows investigating the effect of eutrophication on seagrass performance and their nitrogen uptake capacity. We tested how a 4‐week in situ nutrient enrichment affected inorganic nitrogen uptake rates of a multispecies seagrass meadow in eutrophic and non‐eutrophic seasons, in light and in darkness. All species maintained nitrogen uptake in the dark and preferred ammonium over nitrate. In the eutrophic season, the seagrass leaf biomass and growth were lower resulting in a lower nitrogen filter capacity. Among the species present, Cymodocea rotundata and Cymodocea serrulata covered 48% and 45%, respectively, of their daily nitrogen demand for leaf growth through leaf uptake from the water column, while it was only 30% for Thalassia hemprichii , the last remaining species in meadows degraded by eutrophication, as deduced from previous studies. It indicates that a multispecies seagrass meadow has a higher nitrogen filter capacity than a monospecific T. hemprichii meadow. By reducing seagrass diversity and, hence, the nitrogen filter function, eutrophication triggers a self‐reinforcing process. Once the nitrogen filtering capacity of a seagrass meadow is exhausted, further eutrophication and seagrass loss are expected.

Editorial: Changing biogeochemical and ecological dynamics in the South China Sea in times of global change - Shuwen Zhang; Tim C. Jennerjahn; Fajin Chen; Guangzhe Jin (Frontiers in Marine Science, 2023)

Citizen science to support coastal research and management: Insights from a seagrass monitoring case study in Hainan, China - Jialin Zhang; Shiquan Chen; Cheng Cheng; Yan Liu; Tim C. Jennerjahn (Ocean & Coastal Management, 2023)

Intertwined effects of climate and land use change on environmental dynamics and carbon accumulation in a mangrove‐fringed coastal lagoon in Java, Indonesia - K. Anggi Hapsari; Tim C. Jennerjahn; Martin C. Lukas; Volker Karius; Hermann Behling (Global Change Biology, 2020)
The identification and quantification of natural carbon (C) sinks is critical to global climate change mitigation efforts. Tropical coastal wetlands are considered important in this context, yet knowledge of their dynamics and quantitative data are still scarce. In order to quantify the C accumulation rate and understand how it is influenced by land use and climate change, a palaeoecological study was conducted in the mangrove‐fringed Segara Anakan Lagoon (SAL) in Java, Indonesia. A sediment core was age‐dated and analyzed for its pollen and spore, elemental and biogeochemical compositions. The results indicate that environmental dynamics in the SAL and its C accumulation over the past 400 years were controlled mainly by climate oscillations and anthropogenic activities. The interaction of these two factors changed the lagoon's sediment supply and salinity, which consequently altered the organic matter composition and deposition in the lagoon. Four phases with varying climates were identified. While autochthonous mangrove C was a significant contributor to carbon accumulation in SAL sediments throughout all four phases, varying admixtures of terrestrial C from the hinterland also contributed, with natural mixed forest C predominating in the early phases and agriculture soil C predominating in the later phases. In this context, climate‐related precipitation changes are an overarching control, as surface water transport through rivers serves as the “delivery agent” for the outcomes of the anthropogenic impact in the catchment area into the lagoon. Amongst mangrove‐dominated ecosystems globally, the SAL is one of the most effective C sinks due to high mangrove carbon input in combination with a high allochthonous carbon input from anthropogenically enhanced sediment from the hinterland and increased preservation. Given the substantial C sequestration capacity of the SAL and other mangrove‐fringed coastal lagoons, conservation and restoration of these ecosystems is vitally important for climate change mitigation.

High-resolution multi-proxy reconstruction of environmental changes in coastal waters of the Java Sea, Indonesia, during the late Holocene - Anastasia Poliakova; Karin A.F. Zonneveld; Lucia S. Herbeck; Tim C. Jennerjahn; Haryadi Permana; Cornelia Kwiatkowski; Hermann Behling (Palynology, 2017)

Two‐step vegetation response to enhanced precipitation in Northeast Brazil during Heinrich event 1 - LYDIE M. DUPONT; FRANK SCHLÜTZ; CAROL TEBOH EWAH; TIM C. JENNERJAHN; ANDRÉ PAUL; HERMANN BEHLING (Global Change Biology, 2010)
High resolution palynological and geochemical data of sediment core GeoB 3910‐2 (located offshore Northeast Brazil) spanning the period between 19 600 and 14 500 calibrated year bp (19.6–14.5 ka) show a land‐cover change in the catchment area of local rivers in two steps related to changes in precipitation associated with Heinrich Event 1 (H1 stadial). At the end of the last glacial maximum, the landscape in semi‐arid Northeast Brazil was dominated by a very dry type of caatinga vegetation, mainly composed of grasslands with some herbs and shrubs. After 18 ka, considerably more humid conditions are suggested by changes in the vegetation and by C org and C/N data indicative of fluvial erosion. The caatinga became wetter and along lakes and rivers, sedges and gallery forest expanded. The most humid period was recorded between 16.5 and 15 ka, when humid gallery (and floodplain) forest and even small patches of mountainous Atlantic rain forest occurred together with dry forest, the latter being considered as a rather lush type of caatinga vegetation. During this humid phase erosion decreased as less lithogenic material and more organic terrestrial material were deposited on the continental slope of northern Brazil. After 15 ka arid conditions returned. During the humid second phase of the H1 stadial, a rich variety of landscapes existed in Northeast Brazil and during the drier periods small pockets of forest could probably survive in favorable spots, which would have increased the resilience of the forest to climate change.

Segara Anakan, Java, Indonesia, a mangrove-fringed coastal lagoon affected by human activities - Tim C. Jennerjahn; Edy Yuwono (Regional Environmental Change, 2009)

Spatio-temporal variation of dissolved inorganic nutrients related to hydrodynamics and land use in the mangrove-fringed Segara Anakan Lagoon, Java, Indonesia - Tim C. Jennerjahn; Bushra Nasir; Insa Pohlenga (Regional Environmental Change, 2009)

Relevance of mangroves for the production and deposition of organic matter along tropical continental margins - Tim C. Jennerjahn; Venugopalan Ittekkot (The Science of Nature, 2002)